Congenital Perineal Lipoma-like Lipoblastoma - Nidhi Mahajan; Arti Khatri; Parveen Kumar; Sadia Khanam (Mazandaran University of Medical Sciences, 2020)
Introduction: Adipocytic tumors and its variants are common neoplasms of adults; however, they are rarely seen in paediatric age group, too.  Lipoblastoma typically occurs in children and are diagnosed by the presence of a multivacuolated lipoblast. However, things get complicated when one has to search for these lipoblasts in a background of classical lipoma. As a result, such cases are misdiagnosed and managed inappropriately. We report the first case of a congenital lipoma like lipoblastoma with an unusual presentation. Case Presentation: A 10-day-old male was admitted to the Paediatric Surgery Outpatient Department with a mass in his perianal region since birth. On examination, the mass was non-tender, pedunculated, and located at the margin of the anal opening. A provisional clinical diagnosis of anal tag was made, and swelling was excised. Grossly, we received a skin covered soft tissue mass measuring 1.2cm in diameter. The cut section was yellow and had a soft to firm consistency. Histopathological examination showed a well-delineated moderately cellular lesion comprising of lobules of adipocytes in varying stages of maturation; large number of mature adipocytes and few interspersed multivacuolated lipoblasts. A final diagnosis of lipoma-like lipoblastoma was made.  Conclusion: Lipoma-like lipoblastoma can be seen as a congenital mass and at unusual sites like the perianal region. An accurate diagnosis of this entity is essential for appropriate management. Histopathology is the gold standard for diagnosis and calls for increased awareness.